Cannabis Use Disorder and Perioperative Outcomes in Major Elective Surgeries: A Retrospective Cohort Analysis. (April 2020) - Goel, Akash; McGuinness, Brandon; Jivraj, Naheed K.; Wijeysundera, Duminda N.; Mittleman, Murray A.; Bateman, Brian T.; Clarke, Hance; Kotra, Lakshmi P.; Ladha, Karim S.
Abstract : Background: Although cannabis is known to have cardiovascular and psychoactive effects, the implications of its use before surgery are currently unknown. The objective of the present study was to determine whether patients with an active cannabis use disorder have an elevated risk of postoperative complications. Methods: The authors conducted a retrospective population-based cohort study of patients undergoing elective surgery in the United States using the Nationwide Inpatient Sample from 2006 to 2015. A sample of 4, 186, 622 inpatients 18 to 65 yr of age presenting for 1 of 11 elective surgeries including total knee replacement, total hip replacement, coronary artery bypass graft, caesarian section, cholecystectomy, colectomy, hysterectomy, breast surgery, hernia repair, laminectomy, and other spine surgeries was selected. The principal exposure was an active cannabis use disorder, as defined by International Classification of Diseases, Ninth Edition, Clinical Modification (ICD-9-CM) diagnostic codes for cannabis dependence and cannabis abuse. The primary outcome was a composite endpoint of in-hospital postoperative myocardial infarction, stroke, sepsis, deep vein thrombosis, pulmonary embolus, acute kidney injury requiring dialysis, respiratory failure, and in-hospital mortality. Secondary outcomes included hospital length of stay, total hospital costs, and the individual components of the composite endpoint. Results: The propensity-score matched-pairs cohort consisted of 27, 206 patients. There was no statistically significant difference between patients with (400 of 13, 603; 2.9%) and without (415 of 13, 603; 3.1%) a reported active cannabis use disorder with regard to the composite perioperative outcome (unadjusted odds ratio = 1.29; 95% CI, 1.17 to 1.42; P < 0.001; Adjusted odds ratio = 0.97; 95% CI, 0.84 to 1.11; P = 0.63). However, the adjusted odds of postoperative myocardial infarction was 1.88 (95% CI, 1.31 to 2.69; P < 0.001) times higher for patients with a reported active cannabis use disorder (89 of 13, 603; 0.7%) compared with those without (46 of 13, 603; 0.3%) an active cannabis use disorder (unadjusted odds ratio = 2.88; 95% CI, 2.34 to 3.55; P < 0.001). Conclusions: An active cannabis use disorder is associated with an increased perioperative risk of myocardial infarction. Abstract : In the United States, administrative data demonstrate that cannabis use disorder has increased in prevalence from 2010 to 2015. Active cannabis use disorder is not associated with a change in overall perioperative morbidity, mortality, length of stay, or costs. However, active cannabis use disorder is associated with a meaningful increase in the risk of postoperative myocardial infarction.Supplemental Digital Content is available in the text.